Exploring Research Approaches and Methodologies in Multimedia: Digital Media, Game Development, Visual Communication Design, Broadcasting, and Animation - Juhana, Agus; Anggelika, Laura; Azis, Farhan Abdul (Jurnal Pendidikan Multimedia (Edsence), 2024)
Research methods are structured procedures designed to address research problems and provide effective solutions. In the multimedia field, researchers often rely on standardized methods, regardless of the specific sub-discipline under investigation. For example, the Multimedia Development Life Cycle (MDLC) is among the most commonly used methodologies. However, the diversity of research areas within multimedia—spanning Digital Media, Game Development, Visual Communication Design, Broadcasting, and Animation—requires tailored and specialized approaches to ensure that research outcomes are precise, impactful, and contextually relevant. This study systematically reviews various research methodologies in the multimedia field by analyzing relevant articles and literature. The results present a comprehensive mapping of diverse approaches and methodologies, categorized according to specific subfields within multimedia. This analysis aims to assist academics, researchers, and professionals in selecting methodologies that align with their research objectives, thereby enhancing the quality and specificity of research outputs.